2020
DOI: 10.1002/ange.202000829
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Predictive Power of the Pauling Rules

Abstract: The Pauling rules have been used for decades to rationalise the crystal structures of ionic compounds. Despite their importance, there has been no statistical assessment of the performances of these five empirical rules so far. Here, we rigorously and automatically test all five Pauling rules for a large data set of around 5000 known oxides. We discuss each Pauling rule separately, stressing their limits and range of application in terms of chemistries and structures. We conclude that only 13 % of the oxides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Pauling’s original formulations were based on the nature of chemical bonds between ions ( 41 ), a very short-range interaction dictated by quantum mechanics ( 42 ). Thus, it is therefore not unexpected that a disordering mechanism will not violate these fundamental chemical rules.…”
Section: Resultsmentioning
confidence: 99%
“…Pauling’s original formulations were based on the nature of chemical bonds between ions ( 41 ), a very short-range interaction dictated by quantum mechanics ( 42 ). Thus, it is therefore not unexpected that a disordering mechanism will not violate these fundamental chemical rules.…”
Section: Resultsmentioning
confidence: 99%
“…Bonded radii determined for metal atoms match the Shannon (1976) radii for more electropositive atoms, but the match decreases systematically as the electronegativities of the M atoms increase. As a result, significant departures from the radius ratio rule in the analysis by George et al (2020) is not surprising. We offer a modified, more fundamental version of Pauling's first rule and demonstrate that the second rule has a one-to-one connection between the electron density accumulated between the bonded atoms at the bond critical point and the Pauling bond strength of the bonded interaction.…”
mentioning
confidence: 90%
“…In addition, Gibbs et al (2013a) found strong evidence that the Pauling bond strength-bond length of a M-O bonded interaction is very similar to the average accumulation of the electron density at the bond critical point (<r(rc)>) between bonded pairs of metal and oxygen atoms. On the basis of the correspondence between equations relating <r(rc)> [<R(M-O)> = 1.46<r(rc)>/r -0.19 ] and <s> [<R(M-O)> = 1.46<s>/r -0.21 ] to bond length, Gibbs et al (2013a) Manuscript #7938R (Correction Date 07/14/2021) Gibbs, Hawthorne, Brown One of our motivations for writing this review paper is to address a recent paper by George et al (2020) entitled "The Limited Predictive Power of the Pauling Rules", which questions the applicability of Pauling's first and second rules in particular, based on a statistical analysis of the success of Pauling's rules when applied to 5000 or so crystal structures in the Inorganic Crystal Structure Database. George et al (2020) make the following comment: "Our work therefore calls for the development of new empirical rules beyond the almost one-century old Pauling rules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations